Effects of discharge mode and gas composition for plasma‐hydrophilized titanium surface on hydrophilic sustainability. (21st September 2020) - Hirano, Mitsuhiro; Yamane, Misao; Ohtsu, Naofumi
Abstract : Plasma hydrophilization under various conditions was carried out on Ti substrates to investigate the effect of the applied parameters on the hydrophilic sustainability. The plasma was discharged from gases comprising Ar and/or O2 at various ratios using DC and RF modes. Notable differences in the surface morphology by the plasma conditions was hardly found, while the ratio of hydroxide on the surface was influenced by the discharge mode. The hydrophilicity was significantly improved regardless of the treatment conditions, that is, the gas composition and discharge mode. The deterioration of the hydrophilicity was occurred by storing in the ambient atmosphere or distilled water, wherein the deterioration in distilled water was suppressed when using DC as a discharge mode. The hydrophilicity was preserved when the specimens was stored in a physiological solution such as phosphate buffered saline solution due to the adsorption of Na + and Cl − in the solution; its effect was far superior to that contributed by the parameter settings. In conclusion, plasma discharge mode enabled to improve the deterioration of hydrophilicity only slightly.